The effects of flutter kick on active drag during front crawl swimming - Tsunokawa, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
In front-crawl swimming, the swimmer generates propulsive forces by both arm strokes and leg kicks. And the alternating left-right up-down motion of both legs seen in front-crawl swimming is called the flutter kick. It has been reported that the flutter kicking motions increase swimming velocity by 10% compared to without flutter kicking motions (Deschodt et al., 1999). Flutter kick is seen 6-kicks per 1-stroke cycle in short-distance events, and 2 or 4 kicks in the long-distance events. It is unclear whether flutter kicking motions in front-crawl swimming generate propulsive forces, since these motions are primarily in the vertical direction, not in the propulsive direction. In the previous studies, the role of the flutter kick is thought to lift the lower limbs not only to generate propulsion forces (Yanai, 2001). Thus, there is no consensus on the role of flutter kicks, and it is not certain whether it is providing propulsion or reducing active drag. Unfortunately, flutter kicking motions generates bubbles and unsteady turbulence around feet, making it difficult to analyse the motions due to low visibility. In recent studies on front-crawl swimming, researchers have conducted to estimate fluid forces acting on the hand by measuring the pressure distribution on the hand surface (Tsunokawa et al., 2018: Tsunokawa et al., 2019). This method allows for the quantification of hand propulsive forces. As another approach, a method for evaluating active drag acting on the whole body using MRT method has been reported (Narita et al., 2018). Although the analysis of flutter kicking motions in front-crawl swimming is still difficult, clarifying the relationship between different kicking motions and hand propulsive forces and active drag by combining pressure analysis and MRT method could allow for indirect investigation of the role and contribution of the flutter kicking motions in front-crawl swimming. Therefore, the purpose of this study was to examine the role of the flutter kick indirectly by estimating active drag and hand propulsive force by using pressure analysis and MRT method.